Dampak Kadar Hardener Dan Jenis Thinner (Nc) Terhadap Hasil Lapisan Pengecatan Pada Cat Nitrocellulose (Nc) - Fahmy Zuhda Bahtiar; Fahmy Fatra; Heru Sugiantoro; Riko Diki Arwanto (Universitas Negeri Padang, 2023)
This study aims to determine the effect of hardener volume and NC thinner types (super and ND) on the coating results, such as adhesion, gloss, hardness, and gasoline resistance to nitrocellulose paints (NC). This study used 5ml, 10ml, and 15ml of hardener volume variations with super and ND thinner types. The object of this research is nitrocellulose paints. This study found that the best adhesion test was produced at 5ml, 10ml, and 15ml of hardener volumes using super and ND thinners classified as 5B or 0% (percent area removed). For the best gloss test, the hardener volume was 15ml using super thinner with an average yield of 33,3 GU (Gloss Unit). The best hardness test was produced at volumes of 5ml, 10ml, and 15ml using super and ND thinners, while the best result for gasoline resistance testing was produced at volumes of 5ml, 10ml, and 15ml using super and ND thinners. Penelitian ini bertujuan untuk mengetahui pengaruh volume hardener dan penggunaan thinner jenis NC (super dan ND) terhadap hasil coating seperti gloss, adhesi, hardness dan gasoline resistance terhadap cat NC. Penelitian ini menggunakan variasi volume hardener 5ml, 10ml dan 15ml dengan penggunaan jenis thinner super dan ND. Obyek penelitian ini adalah cat nitroselulosa merek steel gloss. Hasil pada penelitian ini didapatkan bahwa uji adhesi terbaik dihasilkan pada semua variasi volume hardener dengan menggunakan thinner super dan ND yang tergolong klasifikasi 5B atau 0%. Untuk uji kilap terbaik diperoleh pada volume hardener 15ml dengan menggunakan super tiner dengan yield rata-rata 33,3 GU (Gloss Unit). Uji kekerasan terbaik dihasilkan pada semua variasi volume menggunakan tiner super dan ND, sedangkan hasil terbaik untuk pengujian gasoline resistance dihasilkan pada semua variasi volume hardener menggunakan tiner super dan ND.